1-(Piperidin-3-yl)thymine amides as inhibitors of M. tuberculosis thymidylate kinase. (1st January 2019) - Jian, Yanlin; Risseeuw, Martijn D. P.; Froeyen, Mathy; Song, Lijun; Cappoen, Davie; Cos, Paul; Munier-Lehmann, Hélène; van Calenbergh, Serge
Abstract: A series of readily accessible 1-(piperidin-3-yl)thymine amides was designed, synthesised and evaluated as Mycobacterium tuberculosis TMPK ( Mtb TMPK) inhibitors. In line with the modelling results, most inhibitors showed reasonable Mtb TMPK inhibitory activity. Compounds 4b and 4i were slightly more potent than the parent compound 3 . Moreover, contrary to the latter, amide analogue 4g was active against the avirulent M. tuberculosis H37Ra strain (MIC50 =35 µM). This finding opens avenues for future modifications.